Analisis Pengembangan Kurikulum Berbasis Teknologi Digital di SMP YPM 2 Sukodono - Melani, Hesty; Elfarra, Aulya; Karimatul, Ana; Syahri, M.Alfi; Amalia, Kaniati (Lembaga Yasin AlSys, 2023)
The development of information and communication technology is currently very rapid and free competition between countries from all fields, one of which is education. Education personnel and students are guided to keep up with the times in the times in the development of the education curriculum. The study aims to explain and provide an overview of digital technology-based curriculum development at SMPN YPM 2 Sukodono. The application of the method used in this research is descriptive research with a qualitative approach. For data collection techniques, namely by direct research through observation, and interviews then using literature study techniques. In this study, the interview subject was the vice principal of curriculum affairs at SMPN YPM 2 Sukodono. The results obtained in this study indicate that: 1) The application of digital technology in curriculum development at SMPN YPM 2 Sukodono, 2) The role and purpose of digital technology at SMPN YPM 2 Sukodono, 3) Challenges faced in the application of digital technology, 4) Stakeholder relationships in digital technology-based curriculum development. So the conclucion that can be obtained is that the researcher hopes that this research can be useful and beneficial for school principals in developing a digital-based curriculum that is getting better in the future.